Computer Vision Detection and Classification of Emitters for Visible Light Communication - Soto-Gomez, J; Adasme-Soto, P; Zamorano-Illanes, R; Toledo-Mercado, E (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents a methodology for the generation of detection and classification models of light emitters in digital video frames for indoor and outdoor visible light communication applications, including the generation of a user interface for the generation of Datasets of light emitter characteristics. Showing that is possible to analyze the frames of video by applying a classification model, allowing the development of new models to decrease the processing time per frame. © 2021 IEEE.